Exercise biochemistry - Mougios, Vassilis 1958- (Human Kinetics, 2020)
Exercise Biochemistry brings an admittedly difficult and technical subject to life. Extremely user- and student-friendly, it is written in conversational style by Vassilis Mougios, who poses and then answers questions as if in conversation with a student. Mougios does an excellent job of making the information interesting by using simple language without compromising scientific accuracy and content. He also uses ample analogies, related works of art, and numerous illustrations to drive home his points for readers. The result is that Exercise Biochemistry is a highly informative and illuminating text on the effects of exercise on molecular-level functioning. It presents the basics of biochemistry as well as in-depth coverage of exercise biochemistry. The book uses key terms, sidebars, and questions and problems posed at the end of each chapter to facilitate learning. It also covers metabolism, endocrinology, and assessment all in one volume, unlike other exercise biochemistry books. In exploring all of these topics, Exercise Biochemistry makes the case for exercise biochemistry to have a stand-alone textbook. In fact, this book will encourage more universities to introduce exercise biochemistry courses to their curricula. Having the necessary topics of basic biochemistry in a single volume will facilitate the work of both instructors and students. Exercise Biochemistry will also be useful to graduate students in sport science who have not been formally introduced to exercise biochemistry during their undergraduate programs. Additionally, it can supplement exercise physiology textbooks with its coverage of the molecular basis of physiological processes. This book is also for physical education and sport professionals who have an interest in how the human body functions during and after exercise. And this book is addressed to health scientists who are interested in the transformations in human metabolism brought about by physical activity. The book is organized in four parts. Part I introduces readers to biochemistry basics, including chapters on metabolism, proteins, nucleic acids and gene expression, and carbohydrates and lipids. Part II consists of two chapters that explore neural control of movement and muscle contraction. The essence of the book is found in part III, which details exercise metabolism in its six chapters. Included are chapters on carbohydrate, lipid, and protein metabolism in exercise; compounds of high phosphoryl transfer potential; effects of exercise on gene expression; and integration of exercise metabolism. In part IV, the author focuses on biochemical assessment of people who exercise, with chapters on iron status, metabolites, and enzymes and hormones. Simple biochemical tests are provided to assess an athlete's health and performance. Exercise Biochemistry is a highly readable book that serves as a source for understanding how exercise changes bodily functions. The text is useful for both students and practitioners alike